The Rice Marketing System in Tidal Farming: A Case Study of Banyuasin Regency - Nasir Nasir; Gusti Fitriyana; Rouli Simanjuntak; Sisva Berti Afriatna; Zulkarnain Nasution (Institut Pertanian Bogor, 2026)
Rice is a commodity that frequently has issues with its marketing strategy. The challenge with rice marketing in tidal areas is the lengthy marketing chain, which makes it inefficient. This study intended to (1) describe the rice marketing system, (2) identify the elements that farmers and marketing institutions evaluate when selecting transaction partners, and (3) determine the efficiency of rice marketing channels. The research was carried out in Banyu Urip Village, Lago District, Banyuasin Regency, using a survey with sampling approach. The analysis method was descriptive, with a focus on marketing efficiency, margins, and farmer shares. The results demonstrate that the rice marketing channels in the rice producing areas during the ebb and flow were separated into three channels: (a) Channel I = Farmers → Collectors → Wholesalers → Retailers → Consumers; (b) Channel II = Farmers → Collectors → Wholesalers → Consumers, and (3) Channel III: Farmers → Collectors → Retailers → Consumers. Farmers and marketing institutions evaluated the following factors when selecting trade partners: (a) Farmers are bound by debt, price, and emotional relationships; (b) Collectors are concerned about grain prices and quality. (c) Wholesalers: rice price and quality, as well as customer ties, (d) Retailers: rice price and quality, payment procedures, and customer ties. All marketing channels are effective, but the most efficient is Channel III (Farmers → Collectors → Retailers → Consumers). Keywords: farming, marketing system, rice, tidal